2019
DOI: 10.1136/bmjopen-2018-023418
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity on Postoperative Outcomes following cardiac Surgery (The OPOS study): rationale and design of an investigator-initiated prospective study

Abstract: IntroductionIncreasing levels of obesity worldwide have led to a rise in the prevalence of obesity-related complications including cardiovascular risk factors such as diabetes, hypertension and dyslipidaemia. Healthcare providers believe that overweight and obese cardiac surgery patients are more likely to experience adverse postoperative outcomes. The body mass index (BMI) is the primary measure of obesity in clinical practice, without accounting for a patient’s level of cardiopulmonary fitness or muscle mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…The prolonged hospital length of stay and increased ventilation time in the obese group of HFrEF patients are consistent with the literature, which often reports extended recovery periods for obese patients [22,23] following CABG. This could be attributed to a higher burden of comorbidities, increased surgical complexity, and the challenges in postoperative care, including ventilation management.…”
Section: Postoperative Outcomes and Laboratory Insightssupporting
confidence: 90%
See 1 more Smart Citation
“…The prolonged hospital length of stay and increased ventilation time in the obese group of HFrEF patients are consistent with the literature, which often reports extended recovery periods for obese patients [22,23] following CABG. This could be attributed to a higher burden of comorbidities, increased surgical complexity, and the challenges in postoperative care, including ventilation management.…”
Section: Postoperative Outcomes and Laboratory Insightssupporting
confidence: 90%
“…The trend toward higher mortality in the obese group echoes the sentiments of several studies that implicate obesity as a factor in increased short-term mortality following CABG. However, the 'obesity paradox'-where obesity, in certain contexts, appears to confer a survival advantage after cardiac events-remains a contentious topic, with some studies suggesting a protective effect of increased BMI in the postoperative period [22,[27][28][29], but is contradicted in other studies [30,31].…”
Section: Complications and Morbiditymentioning
confidence: 99%
“…In conclusion, the impact of BMI has been consistently analysed in studies that aim to identify risk factors for increased early complications and extended length of stay to enhance quality and provide cost-effective means of patient centered care. An ongoing study by Aguiar, et al [16]. (The impact of Obesity on Postoperative…”
Section: American Journal Of Biomedical Science and Research Am J Bio...mentioning
confidence: 99%
“…Outcomes following cardiac Surgery (OPOS) study) aims to better differentiate obese patients who experience fewer complications from those with increased rates of adverse events [16].…”
Section: American Journal Of Biomedical Science and Research Am J Bio...mentioning
confidence: 99%
“…Previous research regarding this association has shown a correlation between acute renal failure and extreme obesity. [13][14][15][16] It is necessary to mention that obesity, by itself, has a negative effect on renal function due to fluid retention, which predisposes to a state of chronic and acute renal insufficiency. 17,18 Serra et al observed that excess adipose tissue correlated with the insulin resistance mechanism.…”
mentioning
confidence: 99%